Critical equation of seedling block falling off in transplanting process and the optimization experiment of rape blanket seedling transplanter - Jiang, Lan; Wu, Chongyou; Tang, Qing; Zhang, Min; Wang, Gang; Wu, Jun (International Journal of Agricultural and Biological Engineering, 2019)
Considering both high efficiency and high seedling standing quality is a significant objective for crop mechanized transplanting. Rape blanket seedling transplanting is an innovative and efficient transplanting technique. However, falling off phenomenon has become a common problem facing rape blanket seedling transplanting fields that causes seedling standing quality decrease and restricts crop growth. In this study, the rape blanket seedling of Ningza-1838 varieties and 35 d of seedling age was taken as the research object. The critical falling off equations of seedling was established by dynamic analysis. Main factors affecting seedling falling off were obtained. The critical value of each factor was calculated which were as follows: the rotation speed of the planting mechanism was 24.6 rad/s, the substrate moisture content was 50.4% and the longitudinal picking seedling quantity was 14.7 mm. Taking the seedling falling off rate as evaluation index, the measured critical value of seedling falling off was determined by high speed photography experiment. Under the condition that substrate moisture content was 55% and the longitudinal seedling quantity was 15 mm, the seedling falling off rate sharply increased when the transplanting mechanism rotation speed was increased from 24 rad/s to 26 rad/s. Under the condition that the rotation speed was 22 rad/s and the longitudinal picking seedling quantity was 15 mm, the seedling falling off rate rapidly decreased when the moisture content was increased from 47% to 53%. When moisture content exceeded 53%, this exhibited no obvious change. Under the condition that the moisture content was 50% and the rotation speed was 22 rad/s, the seedling falling off rate swiftly raised when the longitudinal picking seedling quantity was increased from 14 mm to 17 mm. The experimental results showed that the seedling falling off rate increased significantly near the critical value. The experimental results showed that the seedling falling off rate changed significantly near the critical value. It proved that the model was correct. Response surface experiments with the Box-Behnken design were conducted to determine the optimal combination parameters, which were as follows: substrate moisture content was 56.24%, planting mechanism rotation speed was 22.04 rad/s, and longitudinal picking seedling quantity was 14.91 mm. At this time, the seedling falling off rate was 1.36%, which ensured that seedlings could be transplanted stably under the carrier of seedling needle. The verification test was conducted, and the working parameters were adjusted according to the optimization results in experiment. The results of verification test were highly consistent with the optimization solution. The present study may provide a theoretical method for improving seedling standing quality of rape blanket seedling, and laid a foundation for the popularization and development of rape carpet seedling transplanting.Keywords: rape blanket seedling, transplanter, planting mechanism, seedling falling offDOI: 10.25165/j.ijabe.20191205.4537Citation: Jiang L, Wu C Y, Tang Q, Zhang M, Wang G, Wu J. Critical equation of seedling block falling off in transplanting process and the optimization experiment of rape blanket seedling transplanter. Int J Agric & Biol Eng, 2019; 12(5): 87–96.